Frazemi s poimenovanji za domače živali v notranjskem zagorskem govoru - Koletnik, Mihaela; Šabec, Tina (Slavia Centralis, 2020)
PHRASEMES CONTAINING NAMES OF DOMESTIC ANIMALS IN THE LOCAL DIALECT OF ZAGORJE IN THE NOTRANJSKA REGION The article focuses on fieldwork data on phrasemes that contain the names of domestic animals used in the local dialect of Zagorje in the Notranjska region, which, according to Slovenian dialectology, belongs to the Primorska dialectal group. The analysis comprises seventy phrasemes organized in the form of dictionary entries. We then ascertained whether these phrasemes are listed in the Dictionary of Standard Slovene (SSKJ) or in the Phraseological Dictionary of Slovene (Keber 2011) as well. Twelve of the phrasemes did not occur in the above-mentioned literary sources. The occurrence of these phrasemes in the local dialect of Šentrupert in the Dolenjska region was examined, focusing on differences and similarities in their usage in both dialects. In both local dialectal regions, cattle is the most common animal species, while the dog is the most common animal. This fact illustrates the frequency of direct contact with these animals. In both local dialects, we found locally specific phrasemes that do not occur in literary language.